Educational Interventions Strategy to Promote the Health of Women Experienced Stillbirth - Maryam Allahdadia; Ali Reza Irajpour (Journal of Holistic Nursing and Midwifery)
Introduction: Stillbirth is one of the saddest experiences in a woman s life, which can have a wide range of cognitive, psychological, spiritual and physical consequences. The health system should consider appropriate educational interventions for mothers in critical situations. Objective: The purpose of this study was to determine the educational needs of Iranian women who experienced stillbirth and help them adapt to this event and improve their health as well as their families health. Materials and Methods: This study was conducted using qualitative content analysis. The participants were 15 women with stillbirth experience who were selected through purposive sampling method among the volunteers referring to health centers in Isfahan Province, Iran. The relevant data were collected and by individual interview recording method. The extraction codes were categorized and three main categories extracted in this regard. Results: The analysis of the participants opinions in describing the required education in the case of stillbirth led to the emergence of three main themes; “management of postpartum changes”, “education for the next pregnancy”, and “teaching how to communicate with children”. Based on the findings, many mothers complained of their lack of necessary education in this matter. They believed that if they received their educational needs, they would easier adapt to this experience. Conclusion: According to the results, review and modification of the care program (to provide women s required education) is necessary to promote the health of women experienced stillbirth. Midwives and health care providers should work on the development of educational and counseling programs for women with stillbirth experience and provide better care for these women.